2006
DOI: 10.1063/1.2399939
|View full text |Cite
|
Sign up to set email alerts
|

Giant moment and magnetic anisotropy in Co-doped ZnO films grown by pulse-injection metal organic chemical vapor deposition

Abstract: We report on large magnetic moments of up to 18.9μB∕Co in Co-doped ZnO films grown by pulse-injection metal organic chemical vapor deposition. The magnetic moment saturates easily in perpendicular magnetic fields and is considerably reduced when the magnetic field is applied parallel to the film plane. The saturation moment is largest for a small Co doping concentration of 1% and persists up to a temperature well above 900K. These extraordinary magnetic attributes cannot be explained by the spin-only moment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 18 publications
2
18
0
Order By: Relevance
“…Similar trend was observed in the Zn 1Àx Co x O films by Zukova et al [5], and Khare et al [20]. When the Co concentration increases the intensity of the (0 0 2) peak decreases with increase in full width at half maximum (FWHM).…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…Similar trend was observed in the Zn 1Àx Co x O films by Zukova et al [5], and Khare et al [20]. When the Co concentration increases the intensity of the (0 0 2) peak decreases with increase in full width at half maximum (FWHM).…”
Section: Resultssupporting
confidence: 63%
“…Coey et al predicted that the magnetic anisotropy is presumably due to new type of ferromagnetism-related defects at the film-substrate interface [35]. The recent observation refers that the origin of magnetic anisotropy may possibly arise from orbital states in a defect-related impurity band [5]. It is also argued that the magnetization anisotropy is due to the trapping of a large number of electrons in orbital states could facilitate an increase of the spin-orbit interaction strength due to symmetry breaking at lattice defects [36].…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…32 A power-law decay is reported for the magnetic moment of ZnO during storage in air. 33 It is suggested that these relaxations can be ascribed to Arrhenius type behavior with a distribution of diffusion-site energies. 34 Detailed electronic structure calculations are still necessary to clarify the role of hydroxyls for a particular oxide.…”
Section: Discussionmentioning
confidence: 99%
“…Beginning with the claim of room temperature ferromagnetism in laser-ablated films of Co-doped anatase TiO 2 [4], there have been many studies on development of ferromagnetic order at room temperature in a range of transition metal doped semiconducting oxides, including TiO 2 , ZnO, SnO 2 and In 2 O 3 [5][6][7][8][9]. This ferromagnetism typically persists above T ¼ 300 K, and the moment per transition metal dopant can exceed the spin-only value in some cases [10][11][12]. However, it has been observed that the magnetic properties are extremely sensitive to sample preparation and measurement techniques, leading to concerns that in many cases ferromagnetism may not be intrinsic but arises from impurity clusters.…”
mentioning
confidence: 99%